Keragaman Kaidah Dharar Sebagai Landasan Hakim Dalam Memutus Permohonan Dispensasi Kawin; Studi Putusan Perkara Nomor 82/Pdt.P/2023/PA.Pmk: The diversity of dharar rules as a basis for judges in deciding applications for marriage dispensation; case verdict study no. 82/rev.p/2023/pa. Pmk - M Ainun Najib Qosim; Mohammad Alif Lukman Hakim; Ilham Yulian Syah Dwi Rachmatullah; Fita Fazalia Rohmah (ISTIDLAL, 2023)
Changes in the age of marriage in positive law in Indonesia, which was marked by the passing of Law no. 16 of 2019 as a change from Law no. 1 of 1974 seems to be the main trigger for the increase in requests for dispensation of marriage in the Religious Courts. This is of course a challenge for the Judge who will decide on the Marriage Dispensation application, for example case number 82/Pdt.P/2023/PA.Pmk, in which case the Judge is faced with two facts that if granted it will disrupt the child's development , and if it is rejected there are fears that unwanted things will happen in the form of adultery. The purpose of this study is to offer new rules that can be taken into consideration by judges in deciding applications for dispensation of marriage. Normative-empirical is the method used in this research. The results of the study show that judges have limited space in using rules as the basis for deciding applications for marriage dispensation, because new rules are needed that can be used as a basis for judges to have more complex considerations.